Penerapan Latihan Sepeda Statis Intradialitik dalam Memperbaiki Gejala Kelelahan pada Pasien Hemodialisis (Journal of Telenursing (JOTING), 2024)
This study aims to implement an intradialytic stationary bicycle exercise intervention to improve fatigue symptoms in hemodialysis patients. The research method used is a literature review. Research results The research results showed that there were significant differences between the experimental group and the control group on fatigue subscales such as decreased motivation (P = 0.02) and mental fatigue (P = 0.046). Also, there were significant differences between the experimental and control groups in all fatigue subscales during the third month of intervention and 1 month after intervention. In addition, the results showed that exercise prevented the development of mental fatigue in the experimental group. In conclusion, exercise with a stationary bicycle prevented an increase in fatigue and its subscales, especially mental fatigue, in the test group. Keywords: Hemodialysis, Fatigue, Stationary Bike